PENGARUH KECERDASAN LOGIS-MATEMATIS DAN EFIKASI DIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 3 SUNGGUMINASA: The Effect Of Logical-Mathematic Intelligence And Self-Efficacy On Mathematics Learning Outcomes Of Class Vii Students Of Smp Negeri 3 Sungguminasa - Halim, St Nur Humairah; Ainun, St Aysah; Mahmud, Randy Saputra (Universitas Tadulako, 2023)
This research aims to determine the influence of logical-mathematical intelligence and self-efficacy on mathematics learning outcomes. This study is quantitative research using an ex-post facto method. The population for this research consists of 341 students, and the sample size is 85 students. The research instruments include questionnaires for assessing logical-mathematical intelligence and self-efficacy, as well as a mathematics learning achievement test on the topic of integers. The data analysis methods used are simple linear regression analysis and multiple linear regression analysis. The results of this study indicate that for the distributed logical-mathematical intelligence questionnaire, the highest score obtained was 96, and the lowest score was 59, resulting in an average score of 77.69, categorized as moderate. For the distributed self-efficacy questionnaire, the highest score obtained was 104, the lowest score was 60, and the average score was 80.67, categorized as high. In the mathematics learning achievement test for the 7th-grade students of SMP Negeri 3 Sungguminasa, the overall average score was 62.69 out of 85 students, with the highest score of 100 and the lowest score of 34, categorized as low. Regarding the simple regression analysis, (1) logical-mathematical intelligence has a significant effect on mathematics learning outcomes with a value of 0.186, and (2) self-efficacy has a significant effect on mathematics learning outcomes with a value of 0.193, indicating no partial influence. In the multiple regression analysis, (3) both logical-mathematical intelligence and self-efficacy simultaneously influence mathematics learning outcomes.